Economic variables and their relationship to the returns of listed and unlisted commercial properties in South Africa - Lin, Che Wei Joey (Department of Construction Economics and Management, 2015)
The purpose of this research is to investigate the relationship between unlisted and listed commercial property returns and the macroeconomic factors identified, which are the stock market, economic activity, inflation and interest rates, in South Africa for the period from 1995 to 2013 (for unlisted properties) and from 2002 to 2013 (for listed properties). It is commonly understood that relevant macroeconomic variables impact asset prices; it is therefore easy to see why it is important to examine the dynamic interactions between the macroeconomic variables and property returns. Previous studies identified stock market performance, economic growth, interest rate and inflation as significant macroeconomic variables. The empirical research in this work is conducted using regression and vector auto regression (VAR) methodologies consistent with prior studies. Regression analysis considers the statistical dependence of the dependent variable on one or more explanatory variables. VAR analysis permits inferences to be drawn about how a particular variable helps to explain property returns and to see how a shock from the same variable affects that return. The work concluded that unlisted property has insufficient historical data to perform the relevant statistical testing. It also established that unlisted property has shown a high correlation (69%) to listed property. Finally, for listed property it was determined that interest rates were found to be a significant negative variable. This result was consistent with the impulse response analysis conducted. Variance decomposition also showed that the interest rate variable explained almost 49% of the volatility of listed property. No other economic variables identified in this work were found to be statistically significant. This research is the first of its kind relating to commercial property in South Africa. The findings of this research reaffirm the theoretical argument that the relationship between interest rates and returns of commercial property is negative. The findings of this research are of significance to investors, analysts and policymakers wishing to acquire a better understanding of this market.